Physiotherapeutic performance in tuberous sclerosis associated with lymphangioleiomyomatosis (Research, Society and Development, 2022)
Tuberous sclerosis is a rare disease, of genetic and degenerative character, where there are anomalies in the TSC1 or TSC2 genes, of chromosomes 9 and 16. Secondary to the pathophysiological process of this disease, pulmonary lymphangioleiomyomatosis (LAM) can occur, a low-grade neoplasm characterized by the proliferation of smooth muscle cells in the lung parenchyma, which can cause several clinical manifestations, such as: spontaneous and recurrent pneumothorax, dyspnea, cough and reduced functional capacity of the individual. Thus, patients have a clinical evolution towards deterioration of lung capacity and respiratory homeostasis disorder.Even with the advancement of medicine, there is still no cure for these diseases. In this study, we report a case of an adult female patient, diagnosed with tuberous sclerosis and pulmonary lymphangioleiomyomatosis, treated at the university hospital in western paraná (HUOP). hospitalization in a patient with tuberous sclerosis and lymphangioleiomyomatosis and thus correlate with the possible benefits of intervention and physical therapy treatment. Patient evolved to discharge improved, active and without the need for oxygen therapy. Therefore, it is concluded that physical therapy is an important ally in helping to treat tuberous sclerosis and lymphangioleiomyomatosis.